Patient Satisfaction and Associated Factors among Clients Admitted to Obstetrics and Gynecology Wards of Public Hospitals in Mekelle Town, Ethiopia: An Institution-Based Cross-Sectional Study - Taklu Marama; Hinsermu Bayu; Mulualem Merga; Wakgari Binu (Hindawi Limited, 2018)
Background. To improve the quality of services, satisfying patients is the primary goal of the Ethiopian reform programme. Objectives. To assess patient satisfaction and associated factors among clients admitted to obstetrics and gynecology wards of public hospitals in Mekelle town. Method: Institution-based cross-sectional study design was conducted on 413 participants using systematic sampling methods. Data were collected from March 9 to May 8, 2016, using structured questionnaires. Data were entered and cleaned in Epidata 3.1 and analysed using SPSS V20 with binary logistic regression model. Result. The observed satisfaction rate was 79.7% at 95% CI (75.8%, 83.6%). Clients were dissatisfied towards well-describing side effects of medication, informing what the medication is used for before prescribing and administering, cleanness of toilet and washroom, and access to drinking water, latrine, and hand-washing facility. Respondents live in rural area, stayed < 4 days, admitted for the first time, admitted in Mekelle General Hospital, and who reported their feeling on ways privacy was assured were more likely satisfied than their counterparts. Conclusions. The observed satisfaction rate is high. So, policymakers, Regional Health Bureau, hospital managers, caregivers, and researchers should plan and work together to keep track of patient satisfaction. Areas patients are dissatisfied should also improve.